Case Report: Extent of the Clinical Spectrum for C9orf72 Mutation - From Frontotemporal Dementia to Autonomic Dysfunction - Catherine Takeda-Raguin; Pierre Olivier Lang; Jérémie Perisse; Nathalie Philippi; Patrick Karcher; Thomas Vogel (Archive of Gerontology and Geriatrics Research - Peertechz Publications, 2017)
C9ORF72 gene mutation on chromosome 9 corresponding to a repetition of hexanucleotides (GGGGCC) xn is the most common mutation found in frontotemporal lobar dementia (FTLD) and amyotrophic lateral sclerosis (SLA) [1]. FTLD is characterized by an insidious onset with gradual evolution, a decline in social and interpersonal behaviors, self-regulation and control disturbances in personal behavior, emotional blunting and loss of introspection capabilities) but also behavioral disorders, disorders of speech and language. Literature is controversial about the relationship between multiple system atrophy (MSA) and the gene C9ORF72 mutation. We report the case of a 70-year old patient diagnosed with familial FTLD with C9ORF72 mutation in 2013 associated with cerebellar syndrome, visual hallucinations, and rapidly progressive symptoms suggestive of MSA.